A Cadaveric Study on Morphometry and Variation of Subclavian Artery: A Cross-Sectional Study - Amgain, Kapil; Adhikari, Shalik Ram; Neupane, Sujana; Panta, Prem Prasad; Sharma, Deepak; Paudel, Tarun; Neupane, Pratima; Sanjel, Seshananda (Journal of Karnali Academy of Health Sciences, 2019)
Background: The subclavian artery is the source of blood supply to the upper limbs. It is the branch of the arch of the aorta on the left side and brachiocephalic trunk on the right side of the neck. It is used as cannulation site for cardiopulmonary bypass and for the insertion of intra-aortic balloon pumps. So its variations in the branching pattern are very important for surgeons and physician as well. Method: The study was conducted on 80 embalmed cadavers over the period of 4 years from August 2013 to August 2017 during the routine dissection for the MBBS and BDS students in dissection hall of anatomy department in Jawaharlal Nehru Medical College, Belgaum, Karnataka, India. The digital vernier calliper was used to measure the morphometric parameter. The data were analysed by using the SPSS version 20. Result: Out of 80 cadavers used for dissection, 52 (65%) were male and 28 (35%) were female. The external diameter of the subclavian artery in male was 7.15mm ± 1.7mm and female was 6.85mm ± 1.5mm with significant sexual dimorphism (p=0.002). The classical course of both subclavian arteries was found in 76 (95%) of the artery and the remaining 5% of the artery was found to have an anomalous course. Conclusion: The subclavian artery in male had a larger diameter than in the female. The variation in the subclavian artery was common. The knowledge of its average size and its anomalous origin, course and branching pattern might be helpful for the surgeon as well as the physician disease diagnosis, interventional therapy, and surgical procedures.